Centennial-scale vegetation dynamics and climate variability in SE Europe during Marine Isotope Stage 11 based on a pollen record from Lake Ohrid - Kousis, Ilias; Koutsodendris, Andreas; Peyron, Odile; Leicher, Niklas; Francke, Alexander; Wagner, Bernd; Giaccio, Biagio; Knipping, Maria; Pross, Joerg (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
To better understand climate variability during Marine Isotope Stage (MIS) 11, we here present a new, centennial-scale-resolution pollen record from Lake Ohrid (Balkan Peninsula) derived from sediment cores retrieved during an International Continental Scientific Drilling Program (ICDP) campaign. Our palynological data, augmented by quantitative pollen-based climate reconstructions, provide insight into the vegetation dynamics and thus also climate variability in SE Europe during one of the best orbital analogues for the Holocene. Comparison of our palynological results with other proxy data from Lake Ohrid as well as with regional and global climate records shows that the vegetation in SE Europe responded sensitively both to long-and short-term climate change during MIS 11. The chronology of our palynological record is based on orbital tuning, and is further supported by the detection of a new tephra from the Vico volcano, central Italy, dated to 410 +/- 2 ka. Our study indicates that MIS 11c (similar to 424-398 ka) was the warmest interval of MIS 11. The younger part of the interglacial (i.e., MIS 11b-11a;similar to 398-367 ka) exhibits a gradual cooling trend passing over into MIS 10. It is characterized by considerable millennial scale variability as inferred by six abrupt forest-contraction events. Interestingly, the first forest contraction occurred during full interglacial conditions of MIS 11c; this event lasted for similar to 1.7 kyrs (406.2 -404.5 ka) and was characterized by substantial reductions in winter temperature and annual precipitation. Most notably, it occurred similar to 7 ka before the end of MIS 11c and similar to 15 ka before the first strong ice-rafted debris event in the North Atlantic. Our findings suggest that millennial-scale climate variability during MIS 11 was established in Southern Europe already during MIS 11c, which is earlier than in the North Atlantic where it is registered only from MIS 11b onwards. (C) 2018 Elsevier Ltd. All rights reserved.